Demand response scheduling to support distribution networks operation using rolling multi-period optimization. (February 2019) - He, Yujun; Petit, Marc
Highlights: A DR scheduling of thermal appliances is proposed to assist the DSO in improving distribution network operation and hosting capacity of DG. The temperature and active power setpoints of DR are determined using a rolling multi-period optimization with the consideration of uncertainties related to the forecasted data. The DR scheduling of thermal appliances has considered the cold load pick-up effect and allows respecting their operational constraints in time series. The use of flexibilities in the distribution network is in a nodal approach. This method can mitigate the violation of voltage and congestion limits, and reduce the reverse power flow due to wind and PV generation. Abstract: This paper presents an approach of demand response (DR) scheduling with thermostatically controlled loads (TCL) in a distribution grid with high penetration of distributed generations (DG). In this approach, household TCL are employed as flexibility resources to support the distribution network for mitigating voltage or congestion constraints. A two-stage rolling optimization based control scheme is proposed to determine the optimal operating status of flexible loads using the forecast of generation and demand in the distribution system. The proposed methodology is conducted in a distribution test feeder with realistic scenarios. The simulation results have shown the usefulness and efficiency of the proposed method in improving the network operation and increasing the hosting capacity of DG.